Appendiceal Recurrent Colic Due to Enterobius Vermicularis Infection in a 14-Year-Old Female Patient - Toni Stoyanov; Emilio Corral-Fernadez; Antonio Melero-Abellan; Pablo Sarduy-Fernandez; Paloma Casado-Santamaria; Elias Garcia-Grimaldo (Journal of Biomedical & Clinical Research, 2016)
Acute appendicitis due to Enterobius vermicularis, usually known as pinworm, is very rare and affects mostly children.According to different authors, it is controversial whether pinworms cause inflammation of the appendix or appendiceal colic only.We presentacase ofa14-year-old female with three subsequent hospitalizations in 1 month due to abdominal pain in the right lower abdomen, with rebound tenderness, normal CTscan and laboratory findings. During the last hospitalization, laparoscopic appendectomy was performed. Intraoperatively multiple pinworms were found in the appendix. These were trapped byastercolith in the appendicular base inanoninflamed and histologically normal appendix. Two oral doses of mebendazole were administered postoperatively. Uneventful postoperative period and postoperative follow-up showed lack of symptoms six months after the operation. Despite the widespread idea that acute appendicitis due to Enterobius vermicularis is very rare, it should always be considered in young female patients with repeated abdominal pain in the right lower abdomen with normal laboratory and radiologic findings.